¿A qué llamamos ficciones?: Ciencias Sociales y Ciencia Ficción. - GALINDO, Dolores Cristina Gomes. (2004)
Preliminary notes on: What do we call fictions? Social science and science fiction. A conference held at the Universitat Autònoma de Barcelona on April 2004 by Alejo Cuervo (Gigamesh science fiction paper editor), Helena Torres & Desiré Rodrigo (Cyberfeminism researchers), Francisco Tirado (UAB lecturer), Martín Mora (Universidad de Guadalajara [Mexico], lecturer) and many other Ph.D students and lecturers that were of great help during the act.